South Shirley Ward Labour Party (covering note) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0047-001 1st July, 1939. Mr. G. Jeger, Spanish Medical Aid Committee, 69, Great Russell Street, London, W.C.1. South Shirley Ward Labour Party With Dr. H.B. Morgan's compliments. Copy letter. Original letter. 292C/946/2/47